Responsabilidad profesional del cirujano odontólogo: ¿qué piensan los abogados? - Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Dossi, Ana Paula; Saliba, Marcos Tadeu Adas; Garbin, Artênio José Isper [UNESP] (Universidad Central de Venezuela, 2010)
The number of lawsuits against dental surgeons has increased considerably in the recent years. Probably this is due to a change in the behavior of the patients, from a passive role in the past to a more demanding stance now. A transversal study was carried out to evaluate the point of view of lawyers in Araçatuba, SP, Brazil, about the professional liability of dentist, the major reasons for treatment failure, the dental specialties more involved in legal actions, their attitudes if they were submitted to an unsuccessful dental treatment, their opinion on what the dentist should do when a patient does not accept the treatment provided, and, finally, what a dentist should do when facing a civil liability action. A questionnaire was sent to 318 lawyers, and 151 of them answered it. The results show that for most lawyers an occasional failure in the treatment occurs due to professional incompetence and, in their opinion, the specialty more involved in legal problems is orthodontics (64.7%). Of the lawyers interviewed, 27.0% affirmed they would seek another dentist and also a lawyer, if they were subjected to an unsuccessful dental treatment. For 36.5% of them, the dentist should give further information and explain the reasons why the treatment did not meet the patient's expectations. According to 36.1% of the interviewees the best policy to be adopted by the dentist in case of a civil liability action would be an extra judicial settlement.

Es cada vez más frecuente el número de acciones judiciales involucrando cirujanos odontólogos. Probablemente este hecho se debe a un cambio de actitud de los pacientes que antes eran sumisos y hoy exigentes. Se realizó un estudio transversal con el objetivo de evaluar la percepción de los abogados de Araçatuba (Sao Paulo) sobre la responsabilidad profesional del cirujano odontólogo, los principales motivos de fracaso durante el tratamiento, las especialidades que más presentan problemas judiciales, la actitud de los mismos si fuesen sometidos a un tratamiento odontológico mal realizado, cual actitud el profesional tiene cuando el paciente no acepta el tratamiento realizado y finalmente la conducta a ser tomada por este delante de una demanda de responsabilidad civil. Se distribuyeron 318 cuestionarios a abogados, de los cuales 151 respondieron. Los resultados prueban que, para la mayoría, una eventual falla en el tratamiento ocurre por la incapacidad del profesional, y en su opinión, la especialidad que más presenta problemas judiciales es la ortodoncia (64,7%). Los abogados como pacientes siendo sometidos a un tratamiento odontológico mal realizado, el 27% procurarían otro cirujano odontólogo y también un abogado. El 36,5% de los entrevistados entienden que si el tratamiento no le agradó al paciente, el profesional debe aceptar la insatisfacción, la inconformidad y descontentamiento del paciente y ofrecer nuevas explicaciones exponiendo los motivos. Para un 36,1% la mejor conducta a ser adoptada por el cirujano odontólogo, en el caso de ser accionado civilmente, sería el intento de un acuerdo extra judicial.
Keywords: Civil liability; Dental surgeon; Malpractice; Responsabilidad civil; Cirujano odontólogo; Abogados